Legal entity identifier accessibility a survey by the trade finance program. - Beck, Steven (ADB briefs.)
Established in 2014 by the Group of Twenty (G20), the LEI is a unique, electronic, 20 digit standard identifier for legal entities, including financial institutions, corporations, governments, and companies. The brief promotes the uptake of the LEI system as a means to increase transparency in the global economy, thwart money laundering and terrorist financing, and help banks conduct due diligence. It also presents the results of a survey that ADB Trade Finance Program conducted to demonstrate that both large and small companies in developing countries can acquire an LEI relatively easily and at reasonable cost.